Hubungan Antara Kondisi Sanitasi Rumah dan Perilaku Penghuni dengan Kejadian ISPA pada Balita di Desa Kayang Kabupaten Alor - Ardian S. Leky; Agus Setyobudi; Christin D. Nabuasa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Acute Respiratory Infections (ARI) is one of the deseases which became the main cause of toddlers’ death. About 13 milion toddlers around the world die every year and the majority of them are from developing country. The risk factors of ARI include factors in the physical environment of the house and the behavior of its residents. The objectives of this study is to analyze the correlation between home sanitation condition and residents’ behaviors with ARI case on toddlers in Kayang village, Alor Regency. The type of this study is cross sectional analytic survey. The population in this study is 102 home with toddlers. The amount of sample is 50 respondents where simple random sampling is used as the sampling technique in this research. This study is conducted on Juni-Juli 2022. Data collection was carried out by interviews and observations using questionnaires and observation sheets. Each independent variables is tested using Chi Square in order to examine the correlation with the dependent variables. The result shows that there is a significant relationship between, ventilation condition (ρ=0.000), kitchen cimey (ρ=0.005), lightening (ρ=0.000), house desity (ρ=0,011), inside-house smoking behavior (ρ=0.000), window-opening behavior (ρ=0.001) with ARI case on toddlers. Whereas ceiling condition (ρ=0.062), floor (ρ=0.989), wall (ρ=0.756), carrying-baby-while-cooking behavior (ρ=0.552) do not have significant correlation with ARI case on toddlers. This study suggests that the resident should repair their broken windows and add air ventilaltion and kitchen chimney, regularly open their windows, avoid smoking inside the house or near the toddlers.